O uso da modelagem aplicada à ergonomia no desenvolvimento de produtos - Pereira, Douglas Daniel [UNESP] (2015)
The ergonomic design deals with man's relationship with the products and systems, methods advocated the use of tests during product development and for this, the use of models is needed, which are often only used for verification, whether morphological, aesthetics, among others. However, the models must also be used for the evaluation of functions of the product. Taking the importance of categorizing the different types of mock-ups, models and prototypes for the different forms of assessment, this study aims to determine which prototyping technique (Traditional and Rapid Protopyping) is best suited to each type of analysis whithin Ergonomic Design of the process. For that they were built 16 models with different techniques and materials that were analyzed and tested with 15 professionals with konowledge of prototypes and product development. Models were evaluated taking into account aspects related to the aesthetic function, function practical and function symbolic. The models were evaluated from the perception of experts and were analyzed statistically using the nonparametric Wilcoxon test, determining as a result the order classification and the groups to which each model belongs as well as its application and different methodologies Ergonomic Design